Effect of biaxial cold pressure densification (BCPD) on Ba0.6K0.4Fe2As2 round wire using optimized precursor. Issue 4 (March 2018) - Li, X.; Collings, E.W.; Wan, F.; Sumption, M.D.; Xue, S.C.; Zhang, D.L.; Rindfleisch, M.A.; Tomsic, M.J.; Shi, Z.X.
Abstract: (Ba, Sr)1- x K x Fe2 As2 superconductor is of great interest as a wire for practical applications. In this paper, Ba0.6 K0.4 Fe2 As2 precursor powder was prepared by high-energy ball-milling aided sintering (12 h/750 °C). The prepared precursor was drawn to powder-in-tube round wire. Partial as-drawn wires were subjected to biaxial cold pressure densification (BCPD) at 0.5 and 1.0 GPa, followed by an annealing for 1 min/770 °C. According to our results, the BCPD improved the grain connectivity of the BCPDed wires without degrading the superconductivity. A (Ba, Sr)1- x K x Fe2 As2 round-wire record transport critical current density, 1.14 × 10 5  A/cm 2 (4.2 K, 2 T), was observed in our BCPDed samples. Graphical abstract: fx1